Improving land use and land cover monitoring by integrating optical imagery and synthetic aperture radar in fragmented rural landscapes around Nandoni Dam, Limpopo Province, South Africa - Ramoelo, Abel (University of Pretoria, 2024)
Dissertation (MSc)--University of Pretoria, 2024